MSSA brain abscess and pyomyositis presenting as brain tumour and DVT. (30th August 2013) - Narayanan, Maya; Mookherjee, Somnath; Spector, Tara B; White, Andrew Austin
Abstract : A 66-year-old man with a recent radiographic diagnosis of a parietal brain tumour presented with severe left thigh pain that prevented ambulation. On examination, his left anterior thigh was mildly swollen without erythema. Initial concern was for deep vein thrombosis in the setting of brain malignancy or necrotising soft tissue infection. Subsequent imaging and biopsies revealed methicillin sensitive Staphylococcus aureus (MSSA) pyomyositis of the left thigh and MSSA brain abscess.